2006
DOI: 10.1074/jbc.m506812200
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Organization of the Interferon-A Genes Differentially Affects Virus-induced Expression and Responsiveness to TBK1 and IKK∈

Abstract: Virus-induced expression of interferon (IFN)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…Similar results are observed in mammals. Human IRF3 selectively binds to distinct IRF-E motifs within IFNa and IFNb gene promoters (51); however, this factor activates the expression of early-phase IFN genes like IFNb but has no effect on most IFNa gene expression (6,7,51). Similar to DrIRF3, human IRF3 selectively exerts a similarly dual effect on IRF7-mediated IFNa gene expression (7) and an inhibitory effect on IRF1-mediated IFNa4 gene expression (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results are observed in mammals. Human IRF3 selectively binds to distinct IRF-E motifs within IFNa and IFNb gene promoters (51); however, this factor activates the expression of early-phase IFN genes like IFNb but has no effect on most IFNa gene expression (6,7,51). Similar to DrIRF3, human IRF3 selectively exerts a similarly dual effect on IRF7-mediated IFNa gene expression (7) and an inhibitory effect on IRF1-mediated IFNa4 gene expression (5).…”
Section: Discussionmentioning
confidence: 99%
“…5). In mammals, IRF3 possesses a restricted recognizing DNA sequence, but IRF7 has a broader one (51); this selective binding contributes to differential regulation of early-phase IFN genes, including IFNb, and later-phase IFN genes, including most IFNas: the former is primarily controlled by IRF3, and the latter are controlled by IRF7 (6)(7)(8)(51)(52)(53). Considering that the IRF3/7-dependent IFN response is activated from cytosolic locations in most cell types (8), the similar binding and regulatory properties of DrIRF3 and DrIRF7 support our previous notion that RLR pathway-triggered DrIFNF1 expression is primarily regulated by DrIRF3, thereby resembling mammalian IFNb, and DrIFNF3 is primarily regulated by DrIRF7, thereby resembling mammalian IFNas (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription of IFNb requires the formation of a large, higher-order multiprotein complex called the enhanceosome, which consists of multiple promoter-specific transcription factors, associated structural components and basal transcription machinery bound to enhancer DNA (Thanos and Maniatis, 1995b;Kim and Maniatis, 1997;Agalioti et al, 2000;Merika and Thanos, 2001). The IFNb promoter-enhancer region contains four positive (PRDI-IV) and one negative regulatory domains (NRDI): PRDI and III contain the binding sites for IRF-7 and IRF-3, respectively, as well as for other IRF members (Civas et al, 2006); PRDII is recognized by NF-kB heterodimers; and PRDIV by ATF-2 and c-Jun heterodimers (Hiscott et al, 1989;Visvanathan and Goodbourn, 1989;Thanos and Maniatis, 1995a;Chu et al, 1999a). Virus infection leads to the recruitment of histone acetyltransferase co-activators (GCN5 and CBP/p300), as well as the high mobility group protein (HMG 1(Y)), which binds to the minor groove of DNA at four sites within the IFNb enhancer and contributes to the stability of the enhanceosome Maniatis, 1992, 1995a;Yie et al, 1997).…”
Section: Assembly Of the Interferon B Enhanceosomementioning
confidence: 99%
“…Among these three modules, the C module specifically binds IRF-3 but is a weak site for IRF-7 interaction; the B and D modules are primarily required for IRF-7 binding and transactivation. The mouse IFN-A11 gene is poorly induced by virus infection because of nucleotide substitutions that disrupt both the C and D modules in the promoter, thus preventing IRF-3 and IRF-7 binding and activation (8,56,57). It was also suggested that IRF-3 ensures the initial activation of IFN-A4 and IFN-B genes in mouse embryonic fibroblasts and that in a second step, it participates in the amplification of the IFN-A4 and IFN-B genes and transactivation of other IFN-A genes, in cooperation with IRF-7 (50).…”
mentioning
confidence: 99%